1985
DOI: 10.1021/bi00338a026
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-19 nuclear magnetic resonance studies of lipid fatty acyl chain order and dynamics in Acholeplasma laidlawii B membranes. A direct comparison of the effects of cis- and trans-cyclopropane ring and double-bond substituents on orientational order

Abstract: The hydrocarbon chain orientational order parameters of membranes of Acholeplasma laidlawii B, enriched with large quantities of fatty acids containing either a cis or a trans cyclopropane ring or a cis or trans double bond, plus small quantities of one of an isomeric series of monofluoropalmitic acids, were determined via fluorine-19 nuclear magnetic resonance spectroscopy over a range of temperatures spanning the corresponding gel to liquid-crystalline phase transitions (determined via differential scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
22
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…We found that viability was affected to a certain extent under all conditions compared here but that disaccharides, e.g., trehalose, maltose, and lactose, were the best lyoprotectants. This finding is in agreement with observations reported in experiments with other microorganisms (Escherichia coli, Bacillus thuringiensis, and Pseudomonas chlororaphis) that were protected during lyophilization by disaccharides (22,23,28). The molecular mechanism behind the protective effect of disaccharides during freeze-drying is unknown, although it has been suggested that these chemicals protect membrane integrity by replacing water molecules in the membrane during the freeze-drying process (23).…”
Section: Discussionsupporting
confidence: 90%
“…We found that viability was affected to a certain extent under all conditions compared here but that disaccharides, e.g., trehalose, maltose, and lactose, were the best lyoprotectants. This finding is in agreement with observations reported in experiments with other microorganisms (Escherichia coli, Bacillus thuringiensis, and Pseudomonas chlororaphis) that were protected during lyophilization by disaccharides (22,23,28). The molecular mechanism behind the protective effect of disaccharides during freeze-drying is unknown, although it has been suggested that these chemicals protect membrane integrity by replacing water molecules in the membrane during the freeze-drying process (23).…”
Section: Discussionsupporting
confidence: 90%
“…Further reductions in matric water potential could lower the liquid crystalline-tohexagonal phase transition temperature. By increasing the amount of trans unsaturated fatty acids, P. putida may raise this transition temperature (7,29,50) and prevent the formation of hexagonal II phases, which are favored by cis monounsaturated fatty acids, and thus again maintain the membrane in a liquid crystalline phase.…”
Section: Discussionmentioning
confidence: 99%
“…A similar increase of the percentage of 19:0 cy fatty acid with the increase of the acidity of the medium was shown by Ballen et al [2] in R. tropici UMR 1899 and UMR 5050 strains. Mac Donald et al [25] have suggested that cyclopropane fatty acids increase in general the organizational stability of membranes and play a protective role against physiological stress. In E. coli, Grogan and Cronan [12] have shown that cyclopropane fatty acid synthase expression was enhanced by low pH.…”
Section: Discussionmentioning
confidence: 99%